Why are East Germans not More Mobile? Analyzing the Impact of Social Ties on Regional Migration - Peter Bönisch; Lutz Schneider (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Individuals' preferences in transition regions are still shaped by the former communist system. We test this 'Communism legacy' hypothesis by examining the impact of acculturation in a communist regime on social network participation and, as a consequence, on preferences for spatial mobility. We focus on the paradigmatic case of East Germany where mobility intentions seem to be substantially weaker than in the western part. Applying an IV ordered probit approach we firstly find that East German people acculturated in a Communist system are more invested in locally bounded informal social capital than West Germans. Secondly, we confirm that membership in such locally bounded social networks reduces the intention to move away. Thirdly, after controlling for the social network effect the mobility gap between East and West substantially reduces. Low spatial mobility of the eastern population, we conclude, is to an important part attributable to a social capital endowment characteristic to post-communist economies. – – Die Präferenzen von Individuen in Transformationsregionen sind immer noch durch Prägungen des früheren sozialistischen Systems bestimmt. Diese These der sozialistischen Prägung wird im Beitrag getestet, indem untersucht wird, ob sich ein Einfluss der Sozialisation in einem solchen System auf die Akkumulation von Sozialkapital und, als Konsequenz, auf die Präferenzen für räumliche Mobilität nachweisen lässt. Gegenstand der Analyse ist der paradigmatische Fall Ostdeutschlands, wo die Mobilitätsneigung deutlich geringer zu sein scheint als im westlichen Teil. Auf Grundlage einer IV-ordered-probit-Schätzung wird erstens belegt, dass Ostdeutsche, sofern sie im Sozialismus aufgewachsen sind, stärker in lokal gebundenes informelles Sozialkapital investiert sind. Zweitens bestätigt sich die These, dass eine Partizipation in derartigen Netzwerken die Mobilitätspräferenz verringert. Drittens zeigt sich, dass sich nach Kontrolle dieses Netzwerkeffektes der Mobilitätsrückstand der Ostdeutschen substanziell verringert. Die eher geringe räumliche Mobilität der ostdeutschen Bevölkerung erscheint daher zu einem erheblichen Teil den typischen Sozialkapitalmustern post-sozialistischer Gesellschaften geschuldet zu sein.
urn:nbn:de:101:1-201011242741
Keywords: J61; R23; C35; 330; Regional mobility; social capital; East Germany; Regionale Mobilität; Sozialkapital; Ostdeutschland